The Effect of Autogenic Relaxation Therapy on Post-Flood Stress in Communities in Widang District, Tuban District - Munir, Miftahul (Jurnal Midpro, 2020)
Natural disasters can occur around the world including indonesi, a natural disaster that often happens is flooding. Floods can have an impact on a person's life either pleasant or unpleasant will remain on the individuals. Dose that will emphasize the possibility of society especially in elderly. This problem needs to be reused immediately to a normal level and will not remember the past events. The purpose of this study to determine the effect of Autogenic Therapy on stress in the elderly in Patihan Village Widang District Tuban.            The research method used is cross sectional. The population used in this study is Elderly in Patihan Village Widang District Widang in accordance with the inclusion criteria of 25, with a large sample of 20 respondents using simple random sampling technique. Independent variable in this research is autogenic therapy, whereas dependent variable is stress on post-flood lanscas, that is data used in data of Questionnaire  and SOP, research analysis using Wilcoxon test.            The results showed There Characteristics of Autogenic Therapy on stress in elderly in Patihan Village Widang District Tuban. This is evidenced by statistical analysis test results wilcoxon α = 0.05 obtained p value = 0.008 where 0.008 ≤ 0.05 (p ≤ α) Medium degree of significance with a negative direction.The results of this study can be used as an alternative self-treatment or posyandu elderly, in dealing with post-flood stress.